1997
DOI: 10.1111/1468-5973.00037
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management in a Disaster Management Context

Abstract: This paper discusses how the adoption of a systematic risk management framework can enhance disaster management. In the analysis of risk, a focus on the interactions between sources of risk and elements at risk, rather than a pre-occupation with hazards, adds more value to management. Vulnerability is the crucial modifier of consequences and, as such, its analysis highlights critical areas and opportunities for developing effective intervention strategies.Risk communication processes based on community involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 1 publication
0
33
0
Order By: Relevance
“…Resilience planning incorporates this type of implementation and internal controls based on evaluation of risk (Matwyshyn, ). Risk management is also prevalent in hazards work and contingency planning for crisis and emergency management (Corvellec, ; Karagiannis, Piatyszek, & Flaus, ; Salter, ). Adaptive Capacity : The frameworks are meant to continually evolve based on feedback and updating. The risk management framework will allow for continual learning from experience as individual organizations implement the model and update their procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience planning incorporates this type of implementation and internal controls based on evaluation of risk (Matwyshyn, ). Risk management is also prevalent in hazards work and contingency planning for crisis and emergency management (Corvellec, ; Karagiannis, Piatyszek, & Flaus, ; Salter, ). Adaptive Capacity : The frameworks are meant to continually evolve based on feedback and updating. The risk management framework will allow for continual learning from experience as individual organizations implement the model and update their procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of road networks has demonstrated that the vulnerability of a region is not only arbitrarily dictated by existing socioeconomic factors per se but also limited by the spatial organization of the transport system. This type of analysis has strengthened the perception that vulnerability is beyond the likelihood of loss; it also manifests in the geographic dimension that plays an integral role in connecting places [31]. Viewing the vulnerability of a region as the clearance time of evacuation is essentially important for a short-notice evacuation where the location or trajectory of a hazard is predictable and a degree of readiness is available [32].…”
Section: Analysis Of Road Network Vulnerabilitymentioning
confidence: 99%
“…One of the major approaches of disaster risk reduction is through pragmatic disaster risk management planning (Salter, 1997;Christoplos et al, 2001). Disaster management and community planning via public participation have become top priority for the authorities, stakeholders and organizations in many countries all over the world such as in the USA (Pearce, 2003, Haimes, 2012, El Salvador (Bowman and White, 2012), Australia and New Zealand (Gero et al, 2011;Djalante, 2012;Becker et al, 2012Becker et al, , 2013 China (Ye et al, 2012, Shi et al, 2012 and Iran (Amini Hosseini et al, 2009).…”
Section: P Karanikola Et Al: Facing and Managing Natural Disasters mentioning
confidence: 99%